Children of Reunion : Vietnamese Adoptions and the Politics of Family Migrations - Varzally, Allison, 1972- (Book collections on Project MUSE., 2017)
In 1961, the U.S. government established the first formalised provisions for intercountry adoption just as it was expanding America's involvement with Vietnam. Adoption became an increasingly important portal of entry into American society for Vietnamese and Amerasian children, raising questions about the United States' obligations to refugees and the nature of the family during an era of heightened anxiety about U.S. global interventions. Whether adopting or favouring the migration of multiracial individuals, Americans believed their norms and material comforts would salve the wounds of a divisive war.